Can Head Circumference Be Used as a Proxy for Intracranial Volume in Patients With Craniosynostosis?. (May 2019) - Hashmi, Asra; Cahill, Gabrielle L.; Zaldana, Michelle; Davis, Greta; Cronin, Brendan J.; Brandel, Michael G.; Beletsky, Alexander; Taj, Raeda; Buckstaff, Taylor M.; Vinocur, Daniel; Lance, Samuel; Meltzer, Hal S.; et al.
Abstract : Background: Calculation of intracranial volume from neuroimaging can be complex and time consuming. In the adult population, there is evidence suggesting that owing to its strong correlation, head circumference (HC) may be used as a surrogate for intracranial volume (ICV). We were interested in studying the correlation between HC and ICV in patients with craniosynostosis. Methods: After institutional review board approval, a retrospective review was performed on patients with craniosynostosis. GE Healthcare AdW 4.3 volume assessment software was used to calculate ICV and HC based on preoperative computed tomographic scans. Pearson correlation was used to estimate correlation coefficients between ICV and HC for this patient population, with 0 to 0.3 considered a weak correlation, 0.4 to 0.6 considered a moderate correlation, 0.7 to 1 considered a strong correlation, and P < 0.05 was considered statistically significant. Results: A total of 196 craniosynostosis patients were included in this study. There were 121 male and 75 female patients. Seventy-nine patients had metopic, 45 had coronal, 64 had sagittal, and 8 had lambdoid synostosis. Mean age was 8.2 months. Mean HC and ICV were 42.9 cm and 829 cm 3, respectively. Overall, there was a strong correlation between HC and ICV ( r = 0.81). Patients were further categorized by craniosynostosis type. Very strong correlation was obtained for patients with coronal (0.89), metopic (0.98), and lambdoid craniosynostosis (0.97). Strong correlation was obtained for patients with sagittal synostosis (0.73). When categorized by sex, a stronger correlation was obtained for female patients (0.84) compared with male patients (0.80). Statistical significance was reached for all reported correlations. Conclusion: Our preliminary data suggest that a very strong correlation exists between HC and ICV for male and female patients with all types of craniosynostosis, making HC a useful surrogate for ICV in this patient population.